1996
DOI: 10.1007/bf01709363
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of epidemiology and prognostic factors in community-acquired pneumonia

Abstract: Of 342 patients with community-acquired pneumonia, 100 were diagnosed etiologically. In these patients, disease epidemiology, prognostic factors, and influence of antibiotic treatment were analyzed prospectively. Fifty-two patients were treated with a broad-spectrum antibiotic (ceftriaxone), and 48 received a medium-spectrum antibiotic (cefuroxime); some patients in each group also received erythromycin. Streptococcus pneumoniae was the most frequently isolated microorganism (43%), followed by Chlamydia pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
4

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 24 publications
1
15
0
4
Order By: Relevance
“…In a second step, the selection of antimicrobial treatment can follow general patterns of expected pathogens according to pneumonia severity and additional risk factors [41,60,61,[127][128][129][130][131][132].…”
Section: What Classification Should Be Used For Treatment?mentioning
confidence: 99%
“…In a second step, the selection of antimicrobial treatment can follow general patterns of expected pathogens according to pneumonia severity and additional risk factors [41,60,61,[127][128][129][130][131][132].…”
Section: What Classification Should Be Used For Treatment?mentioning
confidence: 99%
“…MENÉ NDEZ et al [14] found that low levels of CRP and PCT, in addition to clinical criteria, seem to increase the likelihood of an absence of severe complications in hospitalised patients with CAP. Furthermore, repeat measurements of CRP after 72 or 96 h from initiation of antibiotic therapy seem to be helpful in identifying patients with treatment failure [15,16]. Future research is needed to define if the Data are presented as n (%).…”
Section: Outcome Definitionmentioning
confidence: 99%
“…Especially with oral use at sub-therapeutic concentrations, antimicrobial drugs rapidly lead to multiple drug resistance amongst enteric commensal microfiora (6). Prevalence of exposure to antimicrobial drugs has been iden tified as a predictor of the development of antibiotic drug resistance (7) and it is now generally accepted that the contin ued use of an antimicrobial drug will lead to an increase in prevalence of drug resistance, not only to that drug but also to others which frequently share a transmissible R-plasmid.…”
Section: Methodsmentioning
confidence: 99%